JURIDICAL ANALYSIS OF PROSECUTION TERMINATION BASED ON THE REGULATION OF THE REPUBLIC INDONESIA PROSECUTOR REGULATION NUMBER 15/2020 CONCERNING ON TERMINATION OF PROSECUTION BASED ON RESTORATIVE JUSTICE - Hendriawan, Muhammad Rizaldi (Acitya Wisesa: Journal of Multidisciplinary Research, 2022)
This research explores the shift from a conventional criminal justice system, which focuses on retaliation, to restorative justice as regulated by the Prosecutor's Office of the Republic of Indonesia under Regulation No. 15/2020. The regulation outlines conditions for terminating prosecution in favor of restorative justice, emphasizing reconciliation over punishment. Using a normative juridical method with statutory, case study, and conceptual approaches, the study highlights the prosecutor's critical role in implementing restorative justice. Beyond their traditional prosecutorial duties, prosecutors act as facilitators to prevent case backlogs in courts by enabling termination of prosecution through mediation. In this system, prosecutors play an active role in reconciling victims and perpetrators. Through penal mediation, they aim to achieve a win-win solution where both parties reach mutual agreements and recovery is prioritized over retribution. The goal is to restore the relationships and conditions disrupted by the offense, ensuring the parties involved return to their original state, fostering justice that is both fair and rehabilitative. This approach reflects a significant transformation in Indonesia's criminal justice system, promoting efficiency and healing rather than focusing solely on punishment.